Preparation method of high-pressure-resistant and impact-resistant aluminum oxide ceramic nanofiltration membrane support

Through high-pressure hydrothermal method and microwave low-temperature sintering technology, combined with nanozirconia and corn starch and other materials, a high-pressure and impact-resistant ceramic nanofiltration membrane support was prepared, solving the stability of ceramic membrane under high pressure and chemical corrosion. It significantly improves the explosion pressure and flexural strength, and supports the large-scale application of ceramic membranes.

CN119215686APending Publication Date: 2024-12-31SUNTAR MEMBRANE TECHNOLOGY (XIAMEN) CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411246191.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing ceramic nanofiltration membrane support is prone to fracture under high pressure and chemical corrosion environments, and the uneven agglomeration of nanosintering additives leads to unstable performance, limiting the service life of ceramic membranes and large-scale applications.

Method used

The nanozirconia particles are uniformly wrapped around the surface and internal cracks of alumina ceramic particles by high-pressure hydrothermal method, and corn starch and PVA are combined through microwave low-temperature sintering technology to form a high-pressure and impact-resistant ceramic nanofiltration membrane support.

Benefits of technology

It significantly improves the explosion pressure and flexural strength of the ceramic membrane support, reduces internal defects and unevenness, extends service life, enhances the resistance to high pressure and chemical corrosion, and supports the large nanopore ceramic membrane. Scale application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215686A_ABST
    Figure CN119215686A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-pressure-resistant and impact-resistant alumina ceramic nanofiltration membrane support, which comprises the following steps: firstly, uniformly wrapping the surfaces of alumina ceramic particles with nanoparticles by adopting a high-pressure hydrothermal method, and filling crack defects in the particles; besides, a microwave low-temperature rapid one-time sintering technology is adopted, a uniform and rapid heating mode is utilized, and the nano zirconium oxide particles are stably and rapidly combined into cracks on the surface of the large-particle aluminum oxide ceramic powder and in the particles by combining the high wave absorbing efficiency of the nano zirconium oxide particles (the efficiency is superior to that of large-particle alpha-aluminum oxide). According to the invention, the problems of desorption, agglomeration and segregation of nano-particles possibly occurring in the subsequent mixing, forming and sintering processes are effectively avoided, so that the defects and non-uniformity of the ceramic membrane support body are reduced. Meanwhile, compared with a traditional heating method, more uniform temperature distribution is achieved through microwave heating, and abnormal agglomeration and growth of nanocrystals are prevented.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic membrane support preparation, and specifically relates to a method for preparing a high-pressure and impact-resistant alumina ceramic nanofiltration membrane support. Background Art

[0002] Membrane technology and its related processes are a high-tech field that has rapidly emerged in the middle of the last century and has now become a key part of global scientific and technological innovation and national economic development. Compared with traditional polymer separation membranes, ceramic nanofiltration membranes with high filtration accuracy have been widely used in industries such as petrochemicals, food processing, wastewater treatment, pharmaceutical technology, and energy, and have gradually occupied an important position, becoming one of the key technologies for my country's industrial transformation and upgrading.

[0003] However, the application of ceramic nanofiltration membranes in harsh environments faces many challenges, mainly including: (1) high-pressure operation, which is necessary in high-precision industrial filtration and separation processes to improve filtration efficiency and processing capacity. However, ceramic nanofiltration membranes currently on the market are prone to rupture under high operating pressures, thereby shortening their service life; (2) chemical corrosion problems. When treating liquids containing strong acids, strong alkalis or organic solvents, ceramic nanofiltration membranes must have good chemical resistance. Existing ceramic membrane supports may form internal cracks during the preparation process. These cracks are easily expanded and chemically corroded during use, resulting in membrane tube breakage; (3) mechanical vibration and impact. Ceramic nanofiltration membrane supports are often subjected to these external forces in actual applications, which may cause the expansion of internal cracks and thus cause the membrane support to rupture.

[0004] In the current preparation process of ceramic nanofiltration membrane supports, nano sintering aids need to be added to reduce the sintering temperature of the support, usually by direct mechanical mixing. However, nano sintering aid particles tend to agglomerate, resulting in uneven mixing with large particles of ceramic powder, and segregation during the sintering process, resulting in low strength and large fluctuations of the ceramic membrane tube, and unstable performance (such as Figure 1 As shown). In addition, since the defective cracks of the ceramic aggregate particles are narrow and the crack surface easily absorbs air and moisture after being broken, it is difficult for the agglomerated sintering aid to penetrate into the cracks and cannot be effectively attached. During the sintering process of the support body, the cracks inside these aggregate particles are not covered by the sintering aid and the sintering temperature is not enough to reach the melting temperature, resulting in the cracks being unable to be repaired or sintered together, forming internal crack defects in the finished product. These defects are easily affected by external vibrations and expanded during the transportation and high-pressure use of the membrane tube, which in turn causes the ceramic membrane tube to break and be scrapped. At the same time, these crack defects are also susceptible to chemical corrosion during use, seriously affecting the safety and life of the ceramic membrane tube.

[0005] Ultimately, these problems lead to a series of problems such as many defects in the prepared support, low pass rate, poor product stability, and easy breakage of membrane tubes under the high operating pressure of the ultrafiltration process, which seriously restrict the large-scale application and promotion of nanopore ceramic membranes. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing a high-pressure and impact-resistant alumina ceramic nanofiltration membrane support.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a high-pressure and impact-resistant alumina ceramic nanofiltration membrane support, comprising the following steps:

[0009] (1) mixing a large-particle alumina ceramic powder having an average particle size of 10-45 μm with a nano-zirconia dispersion having a concentration of 5-8 wt%, and reacting the mixture under high-pressure hydrothermal conditions of 8-16 MPa and 300-350° C. for 3-5 hours, wherein the average particle size of the nano-zirconia in the nano-zirconia dispersion is 15-20 nm;

[0010] (2) drying the material obtained in step (1), and then sintering it once at 750-850° C. for 25-35 min using a microwave heating device to obtain alumina powder;

[0011] (3) After sieving the alumina powder obtained in step (2), the alumina powder, corn starch with an average particle size of 0.8-1.2 μm and PVA with an average particle size of 0.8-1.2 μm are mixed evenly, and then RO water and glycerin are added and mixed evenly to form a ceramic mud material and aged;

[0012] (4) vacuum-kneading the material obtained in step (3) using a vacuum kneading machine, and then obtaining a wet blank by extrusion molding;

[0013] (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1830-2050° C. for 3-5 hours to obtain the high-pressure and impact-resistant alumina ceramic nanofiltration membrane support.

[0014] In a preferred embodiment of the present invention, in the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of ZrO2 in the nano-zirconia is greater than 99.9%.

[0015] In a preferred embodiment of the present invention, the drying temperature in step (2) is 120° C. and the drying time is 4 hours.

[0016] In a preferred embodiment of the present invention, the screening in step (3) is through a 120-500 mesh sieve.

[0017] In a preferred embodiment of the present invention, in step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.

[0018] Further preferably, in step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.

[0019] In a preferred embodiment of the present invention, in step (4), the shade drying time is 18-24 hours; the drying temperature is 120° C. and the drying time is 2 hours.

[0020] In a preferred embodiment of the present invention, in the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of ZrO2 in the nano zirconium oxide is greater than 99.9%; in the step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.

[0021] Further preferably, in step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.

[0022] A ceramic nanofiltration membrane comprises a high-pressure and impact-resistant alumina ceramic nanofiltration membrane support body prepared by the above preparation method.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention firstly adopts a high-pressure hydrothermal method to uniformly wrap the nanoparticles on the surface of alumina ceramic particles and fill the crack defects inside the particles. In addition, the present invention adopts microwave low-temperature rapid one-time sintering technology, and utilizes a uniform and rapid heating method, combined with the high wave absorption efficiency of nano zirconium oxide particles (this efficiency is better than that of large-particle α-alumina), to stably and rapidly bond the nano zirconium oxide particles to the surface of large-particle alumina ceramic powder and the cracks inside the particles. This process effectively avoids the problems of nanoparticle desorption, agglomeration and segregation that may occur during subsequent mixing, molding and sintering, thereby reducing the defects and non-uniformity of the ceramic membrane support. At the same time, compared with traditional heating methods, microwave heating achieves a more uniform temperature distribution and prevents abnormal agglomeration and growth of nano grains.

[0025] 2. The present invention only uses nano-zirconia as a sintering aid, and utilizes its reinforcing and toughening effect on alumina to significantly improve the bursting pressure resistance and flexural strength, as well as the impact resistance of the alumina ceramic membrane support.

[0026] 3. The high-pressure and impact-resistant alumina ceramic nanofiltration membrane support prepared by the present invention has achieved a qualitative leap in compressive strength and flexural strength. This not only solves the problems of many microscopic defects, low qualified rate, and poor product stability of existing conventional ceramic nanofiltration membrane supports, but also effectively responds to the challenge of easy breakage of membrane tubes under high operating pressure and frequent impact of filter liquid head in ultrafiltration process, providing a strong technical guarantee for the large-scale application and promotion of nanopore ceramic membranes. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope photograph of a ceramic nanofiltration membrane support body prepared by the existing ceramic nanofiltration membrane support body preparation process in the background technology of the present invention.

[0028] Figure 2 This is a scanning electron microscope photograph of the alumina powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.

[0030] Example 1

[0031] (1) mixing large-particle alumina ceramic powder (purity of Al2O3>99.8%, average particle size of 10 μm) with nano zirconium oxide dispersion (concentration of 8 wt%, purity of ZrO2>99.9%, average particle size of 20 nm), and reacting them under high pressure (16 MPa) hydrothermal (350°C) conditions for 4 h;

[0032] (2) The material obtained in step (1) was dried at 120° C. for 24 h, and then sintered at 850° C. for 30 min using a microwave heating device to obtain alumina powder (such as Figure 2 As shown, microwave heating avoids the problems of uneven temperature distribution and abnormal agglomeration and growth of nano-grains);

[0033] (3) After passing the alumina powder obtained in step (2) through a 500-mesh sieve, the alumina powder, corn starch (average particle size 1 μm) and PVA (average particle size 1 μm) are mixed in a mixer for 4 hours, and then RO water and glycerol are added. After mixing for another 4 hours, ceramic mud is formed and aged for 48 hours, wherein the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76wt%:3wt%:2wt%:16wt%:3wt%.

[0034] (4) The material obtained in step (3) is subjected to vacuum kneading by a vacuum kneading machine, and then a wet blank is obtained by extrusion molding.

[0035] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 20 hours, then slowly heated to 120° C. in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1850° C. for 3 hours to obtain the high-pressure and impact-resistant alumina ceramic nanofiltration membrane support.

[0036] (6) coating one or more layers of filtration membrane on the high-pressure and impact-resistant alumina ceramic nanofiltration membrane support prepared in step (5) by a ceramic filtration membrane preparation process such as dipping or spraying to finally prepare a ceramic nanofiltration membrane.

[0037] According to the relevant test methods in HY / T 064-2002 "Test Methods for Tubular Ceramic Microporous Filter Membranes", the performance of the ceramic nanofiltration membrane is: burst pressure resistance of 34MPa, flexural strength of 39MPa. In comparison, the ceramic nanofiltration membrane based on a ceramic membrane support made by simple mechanical mixing of the same raw materials has a burst pressure resistance of only 11MPa and a flexural strength of only 18MPa.

[0038] Example 2

[0039] (1) mixing large-particle alumina ceramic powder (purity of Al2O3>99.8%, average particle size 45 μm) with nano zirconium oxide dispersion (concentration of 6 wt%, purity of ZrO2>99.9%, average particle size 25 nm), and reacting under high pressure (8 MPa) hydrothermal (300°C) conditions for 4 h;

[0040] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 850° C. for 30 min using a microwave heating device to obtain alumina powder (the specific morphology is basically the same as that of Example 1);

[0041] (3) After passing the alumina powder obtained in step (2) through a 120-mesh sieve, the alumina powder, corn starch (average particle size of 1 μm) and PVA (average particle size of 1 μm) are mixed in a mixer for 4 hours, and then RO water and glycerol are added. After mixing for another 4 hours, ceramic mud is formed and aged for 48 hours, wherein the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 80wt%: 3wt%: 2wt%: 13wt%: 2wt%.

[0042] (4) The material obtained in step (3) is subjected to vacuum kneading by a vacuum kneading machine, and then a wet blank is obtained by extrusion molding.

[0043] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 20 hours, then slowly heated to 120° C. in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 2060° C. for 3 hours to obtain the high-pressure and impact-resistant alumina ceramic nanofiltration membrane support.

[0044] (6) coating one or more layers of filtration membrane on the high-pressure and impact-resistant alumina ceramic nanofiltration membrane support prepared in step (5) by a ceramic filtration membrane preparation process such as dipping or spraying to finally prepare a ceramic nanofiltration membrane.

[0045] According to the relevant test methods in HY / T 064-2002 "Test Methods for Tubular Ceramic Microporous Filter Membranes", the performance of the ceramic nanofiltration membrane is: burst pressure resistance of 31MPa, flexural strength of 36MPa. In comparison, the ceramic nanofiltration membrane based on a ceramic membrane support made of the same raw materials with simple mechanical mixing has a burst pressure resistance of only 7MPa and a flexural strength of only 15MPa.

[0046] Example 3

[0047] (1) mixing large-particle alumina ceramic powder (Al2O3 purity> 99.8%, average particle size 30 μm) with nano zirconium oxide dispersion (concentration of 5 wt%, ZrO2 purity> 99.9%, average particle size 15 nm), and reacting under high pressure (12 MPa) hydrothermal (320°C) conditions for 4 h;

[0048] (2) drying the material obtained in step (1) at 120° C. for 24 h, and then sintering the material at 750° C. for 30 min using a microwave heating device to obtain alumina powder (the specific morphology is basically the same as that of Example 1);

[0049] (3) After passing the alumina powder obtained in step (2) through a 200-mesh sieve, the alumina powder, corn starch (average particle size 1 μm) and PVA (average particle size 1 μm) are mixed in a mixer for 4 hours, and then RO water and glycerol are added. After mixing for another 4 hours, ceramic mud is formed and aged for 48 hours, wherein the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 78wt%: 3wt%: 2wt%: 15wt%: 2wt%.

[0050] (4) The material obtained in step (3) is subjected to vacuum kneading by a vacuum kneading machine, and then a wet blank is obtained by extrusion molding.

[0051] (5) The wet blank obtained in step (4) is dried in the shade at room temperature for 20 hours, then slowly heated to 120° C. in an oven and dried for 2 hours, and then subjected to secondary high-temperature sintering in a high-temperature sintering electric kiln at 1830° C. for 4 hours to obtain the high-pressure and impact-resistant alumina ceramic nanofiltration membrane support.

[0052] (6) coating one or more layers of filtration membrane on the high-pressure and impact-resistant alumina ceramic nanofiltration membrane support prepared in step (5) by a ceramic filtration membrane preparation process such as dipping or spraying to finally prepare a ceramic nanofiltration membrane.

[0053] According to the relevant test methods in HY / T 064-2002 "Test Methods for Tubular Ceramic Microporous Filter Membranes", the performance of the ceramic nanofiltration membrane is: burst pressure resistance of 32MPa, flexural strength of 38MPa. In comparison, the ceramic nanofiltration membrane based on a ceramic membrane support made by simple mechanical mixing of the same raw materials has a burst pressure resistance of only 10MPa and a flexural strength of only 17MPa.

[0054] According to the above examples, the support prepared by the present invention can withstand a bursting pressure of 30-35 MPa and a flexural strength of 35-40 MPa. In contrast, the alumina ceramic nanofiltration membrane support prepared by the prior art method has a bursting pressure of only 6-13 MPa and a flexural strength of only 15-20 MPa.

[0055] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A method for preparing a high pressure and impact resistant alumina ceramic nanofiltration membrane support, characterized in that: The steps include: (1) mixing a large-particle alumina ceramic powder having an average particle size of 10-45 μm with a nano-zirconia dispersion having a concentration of 5-8 wt%, and reacting the mixture under high-pressure hydrothermal conditions of 8-16 MPa and 300-350° C. for 3-5 hours, wherein the average particle size of the nano-zirconia in the nano-zirconia dispersion is 15-20 nm; (2) drying the material obtained in step (1), and then sintering it once at 750-850° C. for 25-35 min using a microwave heating device to obtain alumina powder; (3) After sieving the alumina powder obtained in step (2), the alumina powder, corn starch with an average particle size of 0.8-1.2 μm and PVA with an average particle size of 0.8-1.2 μm are mixed evenly, and then RO water and glycerin are added and mixed evenly to form a ceramic mud material and aged; (4) vacuum-kneading the material obtained in step (3) using a vacuum kneading machine, and then obtaining a wet blank by extrusion molding; (5) The wet blank obtained in step (4) is shade-dried at room temperature, then dried, and then sintered at 1830-2050° C. for 3-5 hours to obtain the high-pressure and impact-resistant alumina ceramic nanofiltration membrane support.

2. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of ZrO2 in the nano zirconium oxide is greater than 99.9%.

3. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 120° C. and the drying time is 4 hours.

4. The preparation method according to claim 1, characterized in that: The sieving in step (3) is through a 120-500 mesh sieve.

5. The preparation method according to claim 1, characterized in that: In the step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.

6. The preparation method according to claim 5, characterized in that: In the step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.

7. The preparation method according to claim 1, characterized in that: In the step (4), the shade drying time is 18-24 hours; the drying temperature is 120° C. and the drying time is 2 hours.

8. The preparation method according to claim 1, characterized in that: In the step (1), the purity of Al2O3 in the large-particle alumina ceramic powder is greater than 99.8%, and the purity of ZrO2 in the nano zirconium oxide is greater than 99.9%; in the step (3), the ratio of alumina powder, corn starch, PVA, RO water and glycerol is 76-80wt%: 3wt%: 2wt%: 13-16wt%: 2-3wt%.

9. The preparation method according to claim 8, characterized in that: In the step (3), the average particle size of the corn starch is 1 μm, and the average particle size of the PVA is 1 μm.

10. A ceramic nanofiltration membrane, characterized in that: The invention comprises a high-pressure and impact-resistant alumina ceramic nanofiltration membrane support body prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Cited By

  • Alumina water treatment ceramic membrane with catalytic function and preparation method thereof

    CN121372052A